Potensi Teknologi Nanopartikel Logam Seng Oksida (NP-ZnO) pada Obat Anti-TB Sebagai Modalitas Mutakhir Pengobatan Penyakit Multidrug-Resistant Tuberculosis (MDR-TB) - Meidina, Adinda Nezma; Triandra, Akbar; Hasibuan, Nabila Az-zahra; Fajri, M. Alif Al (Talenta Publisher, 2024)
Background: Tuberculosis (TB) is a treatable infectious disease caused by the Mycobacterium tuberculosis pathogen. However, patient non-compliance during treatment contributes to the emergence of Multidrug-resistant Tuberculosis (MDR-TB). This literature review aims to further explore the potential of zinc oxide metal nanoparticles (NP-ZnO) in anti-TB drugs as an advanced modality for MDR-TB treatment by enhancing drug efficacy, reducing intestine degradation, and increasing absorption and bioavailability. Methods: Literature was searched using search engines such as Google Scholar, Science Direct, ResearchGate, and NCBI. Inclusion and exclusion criteria were applied, resulting in 14 relevant articles. Results and Discussion: Zinc oxide metal nanoparticles (NP-ZnO) exhibit antibacterial effects. Studies show that NP-ZnO can decrease Rifampicin's minimum inhibitory concentration (MIC) fourfold by enhancing bacterial cell membrane permeability and increasing bactericidal effects through interactions with host macrophage cells. Bactericidal effects were found with NP-ZnO and its combination with selenium (NP ZnO-Se). Meanwhile, bacteriostatic effects on MDR-TB and XDR-TB were observed with NP-ZnO and its combination with silver (NP Ag-ZnO). Conclusion: NP-ZnO encapsulated first-line anti-TB drugs offer advantages in delivering medication to target organs, accelerating therapy onset even with smaller doses, and mimicking M.tb's activity in infecting target organs. NP-ZnO and its combinations are also more sensitive in interacting with alveolar macrophages, the first immune cells responding to M.tb. NP-ZnO encapsulated first-line anti-TB drug technology holds potential as an advanced modality for MDR-TB treatment. Keyword: First-line anti-TB drugs, metal nanoparticle, multidrug-resistant tuberculosis, zinc oxide nanoparticle Â Latar Belakang: Tuberkulosis (TBC) merupakan penyakit menular yang disebabkan oleh patogen Mycobacterium tuberculosis (M.tb) dan dapat diobati, tetapi rendahnya kepatuhan pasien selama pengobatan berdampak pada timbulnya Multidrug-resistant Tuberculosis (MDR-TB). Tinjauan literatur ini bertujuan untuk meninjau lebih lanjut potensi teknologi nanopartikel logam seng oksida (NP-ZnO) pada obat anti-TB sebagai modalitas mutakhir pengobatan penyakit MDR-TB dengan meningkatkan kemanjuran obat yang diberikan, mengurangi degradasi usus, serta meningkatkan absorpsi dan bioavailabilitas. Metode: Literatur dicari menggunakan situs pencari seperti Google Scholar, Science Direct, ResearchGate, dan NCBI. Kriteria inklusi dan eksklusi digunakan untuk mengeliminasi literatur yang tidak berkaitan sehingga diperoleh 14 literatur. Hasil dan Pembahasan: Nanopartikel logam seng oksida (NP-ZnO) menunjukkan efek antibakteri. Studi ini menunjukkan NP-ZnO dapat menurunkan minimum inhibitory concentration (MIC) rifampisin empat kali lipat dengan meningkatkan permeabilitas membran sel bakteri serta meningkatkan efek bakterisida melalui interaksinya dengan makrofag sel inang. Efek bakterisida ditemukan pada NP-ZnO dan kombinasinya dengan selenium (NP ZnO-Se). Sementara itu, efek bakteriostatik MDR-TB dan XDR-TB ditemukan pada NP-ZnO dan kombinasinya dengan perak (NP Ag-ZnO). Kesimpulan: Obat anti-TB lini pertama terenkapsulasi NP-ZnO memiliki keunggulan dalam penghantaran obat ke organ target, mempercepat onset terapi walau dengan dosis yang lebih kecil, dan meniru aktivitas M.tb dalam menginfeksi organ target. NP-ZnO maupun kombinasinya juga lebih sensitif dalam berinteraksi dengan makrofag alveolar yang merupakan sel imun pertama yang merespons M.tb. Teknologi obat anti-TB lini pertama terenkapsulasi NP-ZnO berpotensi sebagai modalitas mutakhir pengobatan MDR-TB. Kata Kunci: Multidrug-resistant tuberculosis, nanopartikel logam, nanopartikel seng oksida, obat anti-TB lini pertama